Antimicrobial efficacy of probiotic-containing toothpastes: an in vitro evaluation - Ivana Parčina Amižić; Livia Cigić; Lidia Gavić; Marina Radić; Dolores Biočina Lukenda; Marija Tonkić; Ivana Goić Barišić (Medicinski glasnik, 2017)
Aim: To evaluate, in vitro antimicrobial ability of two probiotic toothpastes (one containing Lactobacillus paracasei, other containing Lactobacillus acidophilus) and one toothpaste without probiotic separately, and in a combination with two different mouthrinses (one containing essential oils and the other containing hexitidine). Methods: Antimicrobial susceptibility was checked by using the ditch method and Clinical Laboratory Standard Institute (CLSI) guidelines. Two different toothpastes with probiotic, toothpaste without probiotic and two different mouthrinses were tested against the following selected microorganisms: Candida albicans, Candida tropicalis, Enterococcus faecalis, Streptococcus salivarius and Staphylococcus aureus. Kruskal-Wallis test and MannWhitney U test were used for the statistical analysis (p? 0.05). Results: Probiotic toothpastes had better inhibitory effect than toothpaste without probiotic in the case of Candida albicans (p=0.043) and Streptococcus salivarius (p=0.043). In all cases, toothpastes had stronger inhibition capacity than mouthrinses (p?0.05). Conclusion: Probiotic toothpastes, as a relatively new concept in the prevention of oral infectious diseases such as caries and periodontal disease, can contribute to the prevention of oral infectious diseases.
Keywords: Lactobacillus acidophilus; Lactobacillus paracasei; mouthrinse; probiotics